Analysis of Storage Time for Merawang Chicken Eggs (Gallus Gallus) against Hatchability: A Systematic Review - Mafruchati, Maslichah; Makuwira, Jonathan (Jurnal Sain Veteriner, 2024)
Background: Merawang chicken has the potential to be developed, both as local laying hens and local broilers. Hatchability and quality of hatching eggs are influenced by storage method, storage time, storage area, ambient temperature, incubator temperature, reversal during hatching. Storage that is too long causes the quality and hatchability to decrease so eggs should be stored no more than 7 days. Purpose: The purpose of this study was to analyze the length of storage of Merawang chicken eggs (Gallus gallus) on hatchability. Research methods: A literature search was carried out systematically through the PubMed, NCBI, Google Scholar databases using keywords, namely, "Storage Period, Chicken Eggs, Merawang (Gallus Gallus), Hatchability". Based on these keywords, the articles obtained were first selected by setting several inclusion criteria. Research results: Based on the search results in the PubMed, NCBI, Google Scholar databases using predetermined keywords, 15400 articles were obtained for the keywords “Storage Time of Merawang Chicken Eggs (Gallus Gallus), Hatching Power”. All articles were reselected based on inclusion criteria and exclusion and obtained as many as 23 articles that met the inclusion criteria. Conclusion: From the results it can be concluded that the storage time is 9 days (P5) showed hatchability, high fertility and lowest embryo mortality. Need research on the other animal for future research.